2012
DOI: 10.1002/pca.2349
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Ultrasound‐assisted Extraction of Puerarin and Total Isoflavones from Puerariae Lobatae Radix (Pueraria lobata (Wild.) Ohwi) with Response Surface Methodology

Abstract: The RSM allows for optimising the extraction parameters such that maximum extraction of puerarin and total isoflavones was achieved experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Ethanol (60%) was chosen as the lowest solvent concentration in this study. This solvent was chosen because previous studies showed that antioxidant compounds from plant sources were best extracted by 70%–80% ethanol concentrations [2527]. In this study, the kenaf seeds extracted by 80% ethanol had better 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity assay results than the 100% ethanol kenaf seed extract (Table 1).…”
Section: Resultsmentioning
confidence: 82%
“…Ethanol (60%) was chosen as the lowest solvent concentration in this study. This solvent was chosen because previous studies showed that antioxidant compounds from plant sources were best extracted by 70%–80% ethanol concentrations [2527]. In this study, the kenaf seeds extracted by 80% ethanol had better 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity assay results than the 100% ethanol kenaf seed extract (Table 1).…”
Section: Resultsmentioning
confidence: 82%
“…[10] It is less laborious and time-consuming by reducing the number of experimental trials, [11] which makes it widely applied in the extraction process of natural plant and microbiology cultivation research. [12][13][14] Previous investigation has shown Box-Behnken was a useful experimental design to fit a second-order polynomial equation to optimize the extraction process, [15][16][17] and the processing error was almost negligible. Only by reducing system error, the optimal polynomial equation was close to the actual situation.…”
Section: Introductionmentioning
confidence: 99%
“…For solvent to feed ratios below 300, only reduced yields were achieved. Several authors also reported a dependency of extraction yield on solvent to feed ratio . Similarly, they found that an increase of solvent to feed ratio generally leads to an increase of the yield of the target compound.…”
Section: Resultsmentioning
confidence: 88%